Formative experiences in high-school. Between control and innovation in evaluative processes (Praxis Educativa, 2014)
The research presented herein about the formative experiences lived by students and teachers in school gets back to the analysis of an extract related to evaluative actions. We conducted in-depth interviews to students and teachers of a pre-university school in order to figure out the characteristics that evaluative experiences assume in the school, and to study which the logics of action are in relation to the evaluative processes. The analysis of the interviews shows us the marks that the evaluation leaves on the students and the logics which organize the actions of the teachers. Finally we reflect on the emerging, residual and current practices in order to relate them to other formative experiences in the school and to analyze the inequalities in high school and in the educational system.
Keywords: high school; school experiences; evaluation; students; teachers